Recovery in Oil Contaminated Soil (A108D) by Using Subcritical Water (Universitas Negeri Semarang, 2021)
Production activities in the oil and gas industry potentially cause environmental pollution, one of which is soil pollution. Soil contamination is generally found in oil refinery areas due to pipe spills or leaks, spills during tank cleaning or loading-unloading, and oil transportation processes. In this study, the treatment of oil-contaminated soil waste was carried out through oil recovery contained in the soil using water. The treatment process was applied to 3 types of soil waste, that is soil contaminated with oil, sandy soil contaminated with oil, and sludge, with processing times of 30, 60, 90, and 120 minutes, and flow rates of 46, 90, 139, and 183 mL/minute. The water temperature used for processing is ±175 oC with a pressure of 14.5 atm. The results showed that the average decrease in oil content in the samples of oil-contaminated soil, oil-contaminated sandy soil, and sludge, respectively, was 37.7%; 5.8%; and 88.4%. Therefore, the application of this method is most effectively applied to sludge-contaminated soil waste. Based on variations in flow rate and processing time, the longer the processing time, the less oil content in the oil-contaminated soil waste, and the more recovered oil produced. Through the application of the oil recovery system on this oil-contaminated soil waste, the company can save budget, especially the budget for waste treatment reaching Rp 1,142,808.33 per ton. However, some parameters in the liquid waste from this treatment process are above the environmental quality standard so that it needs to be managed further.